Sonoluminiscenca - Srdinšek, Miha (Matrika, 2017)
We speak of sonoluminescence when cavitation bubble in a liquid is driven by sound waves at ultrasound frequency and pressure amplitudes higher than ambient ones. When bubble implodes (most likely) gas in it emits light. Bubble wall dynamics is well described with Rayleigh-Plesset equation. At right degassing of the liquid, driving pressure amplitude and equilibrium radius bubble renounces and than oscillates with resonance frequency, until driving frequency urges it to expand again, because of negative pressure in the antinode and repeats the cycle. When the bubble is expanding, a lot of ambient liquid vaporizes in it, which is important for modeling. Light spectra are continuous and well described with volume emitter model. Temperatures inside the bubble are around 20 000 K or more, pressure around 4000 bar or more and pulse width from 40 to 400 ps. Because of the latter, conclusion is made / reached, that shock wave does not occur. Even though other mechanisms for light emission, such as models based on polarization of the bubble, are proposed, they are not sufficient enough. If driving pressure is weak enough, bouncing bubbles and discrete spectra are observed (due to plasma in the bubble). New experiments, such as sonoluminescence in ?$\rm {H_2SO_4}$?, shine doubt on existing models. A short historic overview of this field of scientific and experimental study is also included in the article.
Keywords: cavitation bubble; kavitacijski mehurček; sonoluminescence; sonoluminiscenca